2006
DOI: 10.1364/opex.14.000001
|View full text |Cite
|
Sign up to set email alerts
|

Bragg localized structures in a passive cavity with transverse modulation of the refractive index and the pump

Abstract: Abstract:We consider a passive optical cavity containing a photonic crystal and a purely absorptive two-level medium. The cavity is driven by a superposition of two coherent beams forming a periodically modulated pump. Using a coupled mode reduction and direct numerical modeling of the full system we demonstrate the existence of bistability between uniformly periodic states, modulational instabilities and localized structures of light. All are found to exist within the conduction band of the photonic material.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…However, when the distance between peaks decreases they start to interact via their oscillating, exponentially decaying tails [4,5,6,7]. LSs have been reported in nonlinear resonators such as lasers with saturable absorbers [8,9,10], in passive nonlinear resonators [2,3,11], optical parametric oscillators [12,13], in left-handed materials [14,15,16,17], in exciton-polariton patterns in semiconductor microcavities [18,19] and in the framework of the Ginzburg-Landau equation [20,21,22,23,24]. Phase solitons have been demonstrated far from any pattern forming instability [25,26,27,28,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…However, when the distance between peaks decreases they start to interact via their oscillating, exponentially decaying tails [4,5,6,7]. LSs have been reported in nonlinear resonators such as lasers with saturable absorbers [8,9,10], in passive nonlinear resonators [2,3,11], optical parametric oscillators [12,13], in left-handed materials [14,15,16,17], in exciton-polariton patterns in semiconductor microcavities [18,19] and in the framework of the Ginzburg-Landau equation [20,21,22,23,24]. Phase solitons have been demonstrated far from any pattern forming instability [25,26,27,28,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Propagation of light beams in various types of nonlinear lattices with modified diffraction has been analyzed [16][17][18][19][20][21][22]. It was demonstrated that light beams can become localized in the periodically curved nonlinear waveguide arrays in the form of diffraction-managed solitons [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…However, nonlinear regimes, including the regimes of Bragg solitons-stable localized structure of high-intensity laser radiation, are undoubtedly promising (Kivshar and Agrawal 2003). More recently, the existence of dissipative solitons in driven nonlinear interferometer with lateral Bragg grating was proved in Staliunas (2003), Yulin et al (2005) and Vladimirov et al (2006).…”
Section: Introductionmentioning
confidence: 99%